Respostas ecofisiológicas e desenvolvimento de cultivares de quiabeiro submetidas a diferentes lâminas de irrigação e adubação orgânica - Santos, Wyayran Fernando Sousa (2021)
The okra, Abelmoschus esculentus (L.), is a vegetable of great importance due to its acceptance in the national market and nutritional value. As it is a rustic and high culture, the edaphoclimatic condition of Brazil favored its development and production. The okra responds in a way to organic fertilization, increases productivity and fruit quality. In addition to fertilizer management, water availability directly affects production, that is, it limits productivity. The present study aimed to evaluate the drought tolerance responses of okra when it occurs under conditions of water scarcity and fertilization, through the analysis of physiological and biometric parameters. The study was conducted in a greenhouse at the Center for Agronomic Biotechnology of the State University of Maranhão (UEMA), the experimental design was completely randomized, in a 2x2x3 factorial scheme, with two okra cultivars (V1- Santa Cruz 47 and V2- Valença), two forms of management (with and without fertilization) and three water regimes: irrigated (L1-100%), moderate (L2-50%) and severe (L3-25%) with 4 replications, the experimental unit being one tested. plant per pot, totaling 48 pots. The fertilized plants that received 100% irrigation, stood out in relation to the other plants in the parameters of intracellular concentration of CO2 (Ci), efficiency of water use (EUA), intrinsic efficiency of water use (EIUA). There were no statistical differences between the varieties in the variables of water use efficiency (EUA), intrinsic water use efficiency (EIUA), intracellular concentration of CO2 (Ci) and the ratio of the intercellular concentration to the ambient concentration of CO2 (ci/ ca ) In the biometric parameters there was a difference between the parameters of Height, Stem diameter, number of lateral branches and crown diameter within each treatment and between Santa Cruz 47 and Valença varieties the similar behavior was similar. Plants that received irrigation blade 100% higher average values of EUA.